1999
DOI: 10.1002/(sici)1097-0258(19990215)18:3<307::aid-sim15>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Semi-parametric estimation of age-time specific infection incidence from serial prevalence data

Abstract: Many infections cause lasting detectable immune responses, whose prevalence can be estimated from cross-sectional surveys. However, such surveys do not provide direct information on the incidence of infection. We address the issue of estimating age and time specific incidence from a series of prevalence surveys under the assumption that incidence changes exponentially with time, but make no assumption about the age specific incidence. We show that these assumptions lead to a proportional hazards model and esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…This is consistent with findings by Dodd et al who suggested estimates of TB infection based on surveys in children may underestimate infection incidence in adults [15]. A higher risk of infection among adolescents than among children of primary school age has also been reported elsewhere [16,17]. In addition, a golden age has previously been described where the incidence of infection goes down after 5 years of age and begins to rise in adolescence [18].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with findings by Dodd et al who suggested estimates of TB infection based on surveys in children may underestimate infection incidence in adults [15]. A higher risk of infection among adolescents than among children of primary school age has also been reported elsewhere [16,17]. In addition, a golden age has previously been described where the incidence of infection goes down after 5 years of age and begins to rise in adolescence [18].…”
Section: Discussionsupporting
confidence: 90%
“…Ades and Nokes [28] used several GLMs to model age and time dependent force of infection for a series of seroprevalence sample of toxoplasmosis. Nagelkerke et al [29] proposed a semiparametric model in which the time (the year of birth) was included as a covariate in the model and the time e ect was estimated parametrically using a proportional hazard model which was applied to a series of tuberculin surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Joint modelling of age and time e ects in the context of infectious disease modelling has been discussed by several authors [12,[14][15][16][17]. Our focus, however, is di erent: temporal e ects are not our primary interest.…”
Section: Introductionmentioning
confidence: 99%